Understanding public attitudes to death talk and advance care planning in Northern Ireland using health behaviour change theory: a qualitative study - L. Graham-Wisener; A. Nelson; A. Byrne; I. Islam; C. Harrison; J. Geddis; E. Berry (BMC, 2022)
Abstract Objectives Advance care planning is a key preparatory step in ensuring high-quality palliative and end of life care, and should be considered as a process, beginning with community-level conversations among lay persons. There is, however, indication that death talk among community-dwelling adults is not occurring, and there is a dearth of research examining why this is the case. This study aims to provide the first examination of barriers and facilitators to talking about death and dying among the general population in a UK region (Northern Ireland), and to provide a novel application of health behaviour change theory towards developing a theoretical understanding of the sources of this behaviour. Methods The study involved qualitative analysis of responses (n = 381 participants) to two open-ended questions within a cross-sectional online survey, with recruitment via social media of adults currently living in Northern Ireland. Reflexive thematic analysis was conducted on open text responses per question, with the barriers and facilitators mapped on to health behaviour change models (the Behaviour Change Wheel COM-B and the Theoretical Domains Framework). Results The findings evidence a myriad of barriers and facilitators to engaging in death talk, with themes aligning to areas such as lack of acceptance of death in social contexts and fear of upsetting self or others, and a need to improve interpersonal communication skills for facilitating conversations and improve knowledge of the existing services around death and dying. A theoretical understanding of the drivers of death talk is presented with findings mapped across most components of the COM-B Behaviour Change Model and the Theoretical Domains Framework. Conclusions This study contributes to a small but emergent research area examining barriers and facilitators to talking about death and dying. Findings from this study can be used to inform new public health programmes towards empowering adults to have these conversations with others in their community towards upstreaming advance care planning.